PELAKSANAAN TUGAS DAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DI DESA TOLITEHUYU KECAMATAN MONANO KABUPATEN GORONTALO UTARA - Gou, Ratna; Kadir , Jusrin; Talalu, Moh Abubakar (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
This research was conducted to find out how the duties and functions of the Village Consultative Body (BPD) in Tolitehuyu Village, Monano District, North Gorontalo Regency are carried out. This research was conducted in Tolitehuyu Village, Monano District, North Gorontalo Regency. This study uses a qualitative approach. The data sources used are primary data and primary secondary data. The number of informants was 7 people, namely the village head, village secretary, BPD chairman, BPD secretary, and 3 community members. Data collection techniques use observation, interviews, documentation. Interactive Model Analysis is used as an analysis method. This model consists of three parts: reducing data, arranging data, and drawing conclusions or verification. The results of the research show that BPD discipline has been running but is not yet optimal because some BPD members rarely attend and sometimes arrive late at village deliberations, while supervision has been running but is not yet optimal because supervision is only carried out by the BPD chairman while BPD members do not participate in supervision and communication. Between the BPD, the village government and the community it is good but not yet running optimally, it's just that the BPD is not very proactive in carrying out its duties, because so far the community has directly conveyed their aspirations to the hamlet head and these have been forwarded by the hamlet head to the village BPD.